Adab dan Ilmu dalam Pandangan Islam: Studi Takhrij dan Syarah Hadis - Leddy Humaira Sakova; Hidayatul Fikra; Mulyana; Raden Roro Sri Rejeki Waluya Jati (Gunung Djati Conference Series, 2022)
This research aims to discuss hadiths about science and adab in the view of Islam, namely the hadith of Ibn Majah No. 220 through the application of takhrij and sharah hadith studies. This research method uses a qualitative approach through literature studies relating to contemporary analysis. The results of the study found that the hadith about science and adab is worth shahih in terms of sanad and matan. From this research can be concluded that science and adab are very important and interrelated, so God placed it as a noble and primary thing. It is also mentioned that high science does not mean if a person does not have fend, so is unable to behave and use his knowledge well. This research recommends further research related to the implementation of Ibn Majah's history hadith No. 220 on science and this adab with different methods and approaches.